Reliability of Panoramic Radiography for Vertical Facial Pattern Assessment - Jeelani, Waqar; Ahmed, Maheen; Ahmed, Shakeel (Journal of Dentistry Indonesia, 2020)
The orthopantomogram (OPG) is a common dental screening radiograph that has multiple implications. However, lateral cephalogram is the investigation of choice for the assessment of vertical facial pattern. Objective: The aim of the current study was to investigate the validity of an OPG parameter i.e. panoramic gonial angle (PGoA) for the assessment of the vertical facial pattern. Methods: A cross-sectional study was conducted on the pretreatment OPG and lateral cephalograms of 200 orthodontic patients aged 15-40 years. The PGoA was measured on both sides and an average was used for statistical analysis. The Pearson’s correlations of PGoA were measured with cephalometric gonial angle (CGoA), SN-GoGn, MMA, FMA, LAFH/TAFH% and PFH/TAFH%. The diagnostic test statistics were applied for PGoA against gold standard “definitive diagnosis (DD)” derived from SN GoGn and FMA. A p-value ofResults: The mean CGoA was 121.18º ± 5.16º which was significantly different (pConclusion: The current study identifies PGoA as a valid tool for the assessment of vertical facial pattern of orthodontic patients with its normal value 116º±3º in our sample.